Heat transfer - Holman, J. P. (The McGraw-Hill Companies, 2002)
This book retains the straight-forward, to-the-point writing style while covering both analytical and empirical approaches to the subject. Throughout the book, emphasis is placed on physical understanding while, at the same time, relying on meaningful experimental data in those situations that do not permit a simple analytical solution.